Analisis Pembelajaran Musik Tabu Gong Rede Geda dalam Konteks Pewarisan Budaya di Desa Riangkotek, Nusa Tenggara Timur - Antonius Harun Ruron; Udi Utomo; Suharto Suharto (Syntax Corporation, 2022)
Tabu gong rede geda music is part of the culture of the Riangkotek village community and is inherited from one generation to another. The inheritance of tabu gong rede geda music uses a tilted inheritance system (Diagonal Transmission), which is an art inheritance system that focuses on learning education. The purpose of this study is to analyze the characteristics of tabu gong rede geda music learning, the components of tabu gong rede geda music learning, and the stages of tabu gong rede geda music learning. Data collection in this study used observation, interview, and document study techniques. Analysis of research data using source triangulation techniques. The results showed that the process of inheritance of tabu gong rede geda music through informail learning. The components of tabu gong rede geda music learning consist of learning participants, instructors, learning objectives, learning materials and learning methods. The learning process consists of four stages, namely seeing and listening, proclaiming, producing, repeatedly.